Extending VTK library to dynamically modify polygonal meshes in medical applications. Issue 2 (4th March 2018) - Vitali, Andrea; Regazzoni, Daniele; Rizzi, Caterina; Colombo, Giorgio
ABSTRACT: Rising reverse engineering applications require the use of 3D models based on polygonal meshes and a set of modeling operations to shape the final product. Usually, 3D modeling tools do not exploit existing software development kits for developing custom virtual applications. This approach can be very useful for reverse engineering process in the medical field. The paper describes the software development of local mesh modeling algorithms as an extension of the open source library VTK with the aim of shaping 3D triangulated meshes. Then, a case study has been considered to create virtual modeling tools supporting the design process of custom-fit products and, in particular, of lower limb prosthetic socket for amputees. The application has been tested to design a socket for a patient with an above knee amputation. Results reached so far provide a positive feedback on the quality of the designed process and outcome, mainly thanks to the use of the virtual tools based on the developed software modules for 3D mesh modeling. GRAPHICAL ABSTRACT: